First record of envenomation by bothrops brazili in the brazilian amazon region - Pereira de Oliveira Pardal, Pedro; Alves Arraes, José Aroldo; Carvalho de Lima, Danielma; Sousa Rocha, Leonardo; Nogueira de Abreu, Elke Maria; Lima de Almeida, Breno Jackson; Borges, Adolfo (Revista de Patologia Tropical / Journal of Tropical Pathology, 2023)
Snakebites in Brazil are most frequently inflicted by Bothrops spp. but there are no records of envenomation by Bothrops brazili. We hereby report on the first confirmed case by this snake, which took place in a primary forest in the State of Pará, in the Brazilian Amazonia, while the victim was felling trees. After being bitten, the man presented with clinical manifestations including pain and edema that extended to the thorax and further complications such as necrosis and abscess. This is the first record of a B. brazili bite in the literature, whose manifestations are similar to those inflicted by other Bothrops spp. with a favorable evolution. KEY WORDS: Snakebite; envenomation; sequelae; Bothrops brazili; Brazilian Amazon.